Effects of Shenfu injection on survival and neurological outcome after out-of-hospital cardiac arrest: A randomised controlled trial. (May 2020) - Shao, Fei; Li, Haibin; Li, Dou; Li, Chunsheng
Abstract: Aim: We aimed to assess the effects of Shenfu injection (SFI) in combination with epinephrine during cardiac arrest on survival and neurological outcome after out-of-hospital cardiac arrest (OHCA). Methods: In this randomised, assessor-blind controlled trial, Utstein-style data were collected from 1233 OHCA patients treated at the Beijing Emergency Medical Center between January 2013 and June 2016. The patients were randomised into either a treatment group that received a combination of SFI and standard treatment with epinephrine or a control group that received standard treatment with epinephrine alone. The primary outcome was survival to hospital admission. The secondary outcomes were return of spontaneous circulation (ROSC), survival to hospital discharge, favourable neurological outcome at discharge, survival to one year, and favourable neurological outcome at one-year survival. Results: In both groups, the survival to hospital admission, ROSC, survival to hospital discharge, and one-year survival rate after discharge from the hospital did not differ significantly. However, SFI achieved favourable neurological outcome at discharge in comparison with the standard treatment with an odds ratio (OR) of 2.72 at a 95% confidence interval (CI; 1.00–8.53). Meanwhile, unlike with epinephrine alone, the combination of SFI and epinephrine achieved a better cerebral performance category (CPC) score (1–2) after one-year survival (OR: 5.08, 95% CI: 1.07–47.80). Conclusion: The combination of SFI and epinephrine had favourable neurological outcomes after OHCA compared with those with epinephrine alone, whereas the survival to admission was not significantly altered.